The query of nursing in the prevention of cervico-uterine cancer for women that experienced - Cilene Nunes Dantas; Bertha Cruz Enders; Pétala Tuani Candido de Oliveira Salvador; Kisna Yasmin Andrade Alves (Rev Rene)
Cervix neoplasm prevention is a practice of a nurse in the health care of women, which should be performed through qualified nursing appointment. Thus, the study aims at identifying the significance of nursing appointment on the prevention of cervix neoplasm held according to the precepts of humanistic nursing for women who have had it. It is a qualitative study that uses methodological referential convergent-search through assisted interviews. Then the perceptions of the patients regarding the experience of nursing consultation in humanistic perspective are described. Thus, the study sees the possibility of a new way to perform rigorous assistance in Humanistic Theory of Paterson and Zderad, which provides a dialogue with the nurses regarding the prevention of cervical cancer.